2021
DOI: 10.30564/jzr.v3i1.2619
|View full text |Cite
|
Sign up to set email alerts
|

The Occurence of Gastrointestinal Helminths in Slaughtered Cattle in Azare,North-East Nigeria

Abstract: A Cross-sectional Study was carried out to determine the prevalence of gastrointestinal (G.I.)  helminths parasites in slaughtered cattle at Azare abattoir, Katagum Local Government Area, Bauchi State, North-Eastern Nigeria. One hundred and twenty faecal samples were examined using the floatation and sedimentation method. Out of the total samples tested, G.I. helminths infections were detected in 62samples tested, giving an overall prevalence of 51.6%. Class nematodes are the most diverse class (56.5%) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
2
3
3
Order By: Relevance
“…were the most abundant gastrointestinal parasites. This agrees with the findings of Umar et al (2021) and Adedipe et al (2014), who also reported some of these trematodes in their studies. The logistic regression analysis of the present study indicates that cattle in the study area are almost sixteen times more likely to be affected by trematodes than cestodes [COR (95% CI): 16.12 (3.78-68.64)].…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…were the most abundant gastrointestinal parasites. This agrees with the findings of Umar et al (2021) and Adedipe et al (2014), who also reported some of these trematodes in their studies. The logistic regression analysis of the present study indicates that cattle in the study area are almost sixteen times more likely to be affected by trematodes than cestodes [COR (95% CI): 16.12 (3.78-68.64)].…”
Section: Resultssupporting
confidence: 93%
“…Regarding cestodes, the total prevalence of Moniezia spp. identified in our study was substantially lower than that reported by Adedipe et al (2014) and Umar et al (2021) in Nigeria at 2.1% and 4.2%, respectively. Moniezia spp.…”
Section: Resultscontrasting
confidence: 85%
See 3 more Smart Citations